Oxidative Imbalance in Candida tropicalis Biofilms and Its Relation With Persister Cells - da Silva, María A.; Baronetti, José L.; Páez, Paulina L.; Paraje, María G. (Frontiers in Microbiology, 2021)
Persister cells (PCs) make up a small fraction of microbial population, can survive lethal concentrations of antimicrobial agents. In recent years, Candida tropicalis has emerged as being a frequent fungal agent of medical devices subject to biofilm infections. However, PCs are still poorly understood. This study aimed to investigate the relation of PCs on the redox status in C. tropicalis biofilms exposed to high doses of Amphotericin B (AmB), and alterations in the architecture of biofilms. We used an experimental model of two different C. tropicalis biofilms exposed to AmB at supra minimum inhibitory concentration (SMIC80), and the intra- and extracellular reactive oxygen species (iROS and eROS), reactive nitrogen species (RNS) and oxidative stress response were studied. Light microscopy (LM) and confocal laser scanning microscopy (CLSM) were also used in conjunction with COMSTAT. We demonstrated that biofilms derived from the PC fraction (B2) showed a higher capacity to respond to the stress generated upon AmB treatment, compared with biofilms obtained from planktonic cells. In B2, a lower ROS and RNS accumulation was observed in concordance with higher activation of the antioxidant systems, resulting in an oxidative imbalance of a smaller magnitude compared to B1. LM analysis revealed that the AmB treatment provoked a marked decrease of biomass, showing a loss of cellular aggrupation, with the presence of mostly yeast cells. Moreover, significant structural changes in the biofilm architecture were noted between both biofilms by CLSM-COMSTAT analysis. For B1, the quantitative parameters bio-volume, average micro-colony volume, surface to bio-volume ratio and surface coverage showed reductions upon AmB treatment, whereas increases were observed in roughness coefficient and average diffusion distance. In addition, untreated B2 was substantially smaller than B1, with less biomass and thickness values. The analysis of the above-mentioned parameters also showed changes in B2. To our knowledge, this is the first study that has attempted to correlate PCs of Candida biofilms with alterations in the prooxidant-antioxidant balance and the biofilm architecture. The finding of regular and PCs with different cellular stress status may help to solve the puzzle of biofilm resistance, with redox imbalance possibly being an important factor.